Aquisição de onsets complexos por crianças de dois a cinco anos: um estudo longitudinal com base na teoria da otimidade - Staudt, Letícia Bello (Universidade do Vale do Rio dos Sinos, 2008)
This paper proposes reflections about language acquisition from children with normal phonologic development, between the ages of 2 and 5, based on Optimality Theory. For being the last structure stabilized in the child linguistic system, the sequence CCV leads to a reflection on the peculiarities of its acquisition, since simpler structures, as V and CV, already are part of the children phonologic system between the age of 1:0 and 1:4. The research describes the complex syllable acquisition by eight informers that are part of researches realized at UNISINOS. It made considerations about outputs that had not evidenced the right form and about the favorable contexts to the correct speech of complex onset. There are also comparisons with studies already done, like Magalhães (2000), Avila (2000), Ribas (2002) and Redmer (2007), among others. According to the analyzed data, the children show two steps during the structure CCV acquisition: production C1V >> production C1C2V. These reflections based on Optimality Theory showed its great explaining power. Then, this study wants to contribute with reflections about the language acquisition for children by 2 to 5, based on Optimality Theory, beyond brings information about phenomena observed on children language.
Keywords: Aquisição fonológica; Onsets complexos; Teoria da Otimidade; Phonological acquisition; Complex onset; Optimality theory; ACCNPQ::Lingüística, Letras e Artes::Lingüística